Relations of postural change in blood pressure with hypertension-mediated organ damage in middle-aged adults of the Framingham heart study: A cross-sectional study - Cooper, Leroy L.; Rong, Jian; Maillard, Pauline; Beiser, Alexa; Hamburg, Naomi M.; Larson, Martin G.; DeCarli, Charles; Vasan, Ramachandran S.; Seshadri, Sudha; Mitchell, Gary F. (Frontiers in Cardiovascular Medicine, 2022)
Background: Dysregulation of compensatory mechanisms to regulate blood pressure (BP) upon postural change is a phenotype of BP variability and an emerging risk factor for cardiovascular outcomes. Methods: We assessed postural change in BP (starting 2 minutes after standing from a supine position), carotid-femoral pulse wave velocity (cfPWV), and markers of hypertension-mediated organ damage (HMOD) in the heart, kidney, and brain in Framingham Third Generation, Omni-2, and New Offspring Spouse Cohort participants. We related vascular measures (postural change in BP measures and cfPWV) with HMOD in 3495 participants (mean age 47 years, 53% women) using multivariable logistic and linear regression models. Results: In multivariable-adjusted models, we did not observe significant associations of vascular measures with presence of left ventricular hypertrophy, albuminuria, covert brain infarcts, or white matter hyperintensities (Bonferroni-adjusted P values >0.05/20>0.0025). In multivariable models, greater cfPWV (est. β=0.11±0.03; P<0.001), but not postural change in BP measures (Bonferroni-adjusted P values>0.05/20>0.0025), was associated with higher white matter free water using brain magnetic resonance imaging. In multivariable models, greater postural change in pulse pressure was associated with higher urinary albumin-creatinine ratio (est. β=0.07±0.02; P<0.001). No other postural change in BP measure was associated with urinary albumin-creatinine ratio (Bonferroni-adjusted P values>0.05/20>0.0025). In sex-specific analyses, higher cfPWV was associated with higher urinary albumin-creatinine ratio in men (est. β: 0.11±0.04; P=0.002) but not in women (est. β: 0.03±0.03; P=0.44). We also observed marginal to strong effect modification by above versus at/below median postural change in BP for the association of cfPWV with urinary albumin‐creatinine ratio (Bonferroni-adjusted interaction P<0.001 to 0.01). Vascular measures were not related to left ventricular mass index or fractional anisotropy (Bonferroni-adjusted P values>0.05/20>0.0025). Conclusions: Baroreflex dysfunction is associated with greater subclinical kidney damage. Additionally, relations of higher aortic stiffness with greater kidney damage may be modified by associated baroreflex dysregulation.